G276(P) Neonatal mortality in western uganda. (12th March 2018) - Harris, C; Patel, H; Corn, O; Harris, U; Munyagwa, M; Greenough, A
Abstract : Aims: Neonatal mortality in Uganda has not improved in the last 14 years and remains between 24 and 27 deaths per 1000 live born infants, which compares poorly to the UK neonatal mortality (2.4 per 1000 live born infants). Our aim was to determine the immediate and long-term impact of introduction of low-cost guidelines on neonatal mortality in a low-income setting. Methods: Neonatal mortality was audited for three months prior to the intervention. The intervention consisted of guidelines developed using a literature review and experience from local doctors, nurses and a visiting paediatrician. The guidelines focused on four areas: (i) ensuring all babies requiring oxygen, antibiotics or fluids were cared for on the neonatal unit, (ii) separating infants with infections from premature infants, improving hand washing techniques and teaching parents to perform observations thus reducing cross contamination, (iii) using antibiotic regimens based on microbiology data and lower thresholds to start antibiotic treatment, (iv) acutely unwell infants were not enterally fed and nasogastric tubes were for premature or neurologically compromised infants. The guidelines were disseminated at a ward meeting at the end of the audit and implemented with ongoing ward based teaching. Mortality was re-audited for the three-month period immediately post implementation. The audit was repeated at the same period of the year three years and six years post intervention. Results: Pre-intervention there were 79 neonatal deaths in the three months with 137 admissions to the neonatal unit (0.58 deaths per admission). Forty-nine neonatal deaths occurred in the three months post intervention with 187 admissions to the neonatal unit (0.26 deaths per admission) (p<0.001). Three years post intervention there were 60 neonatal deaths and 233 admissions to the neonatal unit (0.26 deaths per admission, p<0.001). Six years post intervention, there were 53 neonatal deaths and 315 admissions to the neonatal unit (0.17 deaths per admission, p<0.001). Conclusion: These data demonstrate it was possible to produce a sustained reduction in hospital neonatal mortality in Western Uganda.